Diseño de un circuito con arduino para el monitoreo del estado de temperatura, presión, energía y ubicación de las torres de luz nocturna en Mecánicos asociados S.A.S. (2023)
This degree work proposed the design of a circuit with Arduino to monitor the state of temperature, pressure, energy and location of the night light towers in the company Mecánicossociados S.A.S in the contract for light equipment located in the mine pits. Cerrejón. To achieve the proposed objectives, a descriptive research was carried out. It was determined that the towers were out of operation due to disconnection of the battery due to theft, high temperature, pressure difference, and not having a positioning or geographic location system, the equipment was lost. The circuit design is integrated by an Arduino UNO, three input switches, a GPS module, a virtual terminal, three LED output indicators and a system with a motor. The programming and simulation of the circuit was carried out using Arduino IDE 2.1.0 and Proteus. The cost of the system was estimated at approximately $4,301,869.00 each. Finally, the approximate total cost including the 150 light towers was $645,280,350.00. This design provides an alternative for the immediate attention of the light towers that contribute to the interruptions of the different types of dispersed processes carried out in the mine. Likewise, the technician can identify the light tower in the shortest possible time. What failure and what variable.